Opini Opini Going concern di Sektor Pertambangan: Pengaruh Lag Audit, Opinion shopping, dan Kondisi Keuangan - Denny Putri Hapsari Hapsari; Nana Umdiana Umdiana; Denny Kurnia Kurnia (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam 45, 2025)
This study aims to examine the influence of audit report lag, opinion shopping, liquidity ratio, and financial distress on going concern audit opinion in mining sector companies listed on the Indonesia Stock Exchange for the period 2019–2023. The research adopts a quantitative descriptive approach using logistic regression analysis. The sample comprises 46 companies selected through purposive sampling, resulting in 230 observations. The findings reveal that audit report lag and liquidity ratio significantly influence going concern opinions. Audit lag has a positive effect, indicating that longer audit completion time increases the likelihood of receiving a going concern opinion. Conversely, liquidity shows a negative effect, implying that companies with stronger short-term debt-paying ability are less likely to receive such opinions. Meanwhile, opinion shopping and financial distress show no significant impact. This study highlights the importance of audit timeliness and financial health as key considerations in auditors’ going concern assessments. The findings offer implications for auditors and regulators to emphasize timing and financial ratios when evaluating a company's sustainability. Keywords: going concern opinion, audit lag, opinion shopping, liquidity, financial distress